E-ELT constraints on runaway dilaton scenarios - Martinelli, Matteo; Calabrese, Erminia; Martins, Carlos J. A. P. (Journal of cosmology and astroparticle physics, 2015)
We use a combination of simulated cosmological probes and astrophysical tests of the stability of the fine-structure constant α, as expected from the forthcoming European Extremely Large Telescope (E-ELT), to constrain the class of string-inspired runaway dilaton models of Damour, Piazza and Veneziano. We consider three different scenarios for the dark sector couplings in the model and discuss the observational differences between them. We improve previously existing analyses investigating in detail the degeneracies between the parameters ruling the coupling of the dilaton field to the other components of the universe, and studying how the constraints on these parameters change for different fiducial cosmologies. We find that if the couplings are small (e.g., αb = αV ∼ 0) these degeneracies strongly affect the constraining power of future data, while if they are sufficiently large (e.g., αb ≳ 10−5−αV ≳ 0.05, as in agreement with current constraints) the degeneracies can be partially broken. We show that E-ELT will be able to probe some of this additional parameter space.
Gesehen am 08.06.2020